Nurse practitioners on 'the leading edge' of medication abortion care: A feminist qualitative approach. (11th November 2022) - Carson, Andrea; Cameron, Emma Stirling; Paynter, Martha; Norman, Wendy V.; Munro, Sarah; Martin‐Misener, Ruth
Abstract: Aims: To explore nurse practitioners' experiences of medication abortion implementation in Canada and to identify ways to further support the implementation of medication abortion by nurse practitioners in Canada. Design: A qualitative approach informed by feminist theory and integrated knowledge translation. Methods: Qualitative interviews with stakeholders and nurse practitioners between January 2020 and May 2021. Data were analysed using critical feminist theory. Results: Participants included 20 stakeholders, 16 nurse practitioner abortion providers, and seven nurse practitioners who did not provide abortions. We found that nurse practitioners conduct educational, communication and networking activities in the implementation of medication abortion in their communities. Nurse practitioners navigated resistance to abortion care in the health system from employers, colleagues and funders. Participants valued making abortion care more accessible to their patients and indicated that normalizing medication abortion in primary care was important to them. Conclusion: When trained in abortion care and supported by employers, nurse practitioners are leaders of abortion care in their communities and want to provide accessible, inclusive services to their patients. We recommend nursing curricula integrate abortion services in education, and that policymakers and health administrators partner with nurses, physicians, midwives, social workers and pharmacists, for comprehensive provincial/territorial sexual and reproductive health strategies for primary care. Impact: The findings from this study may inform future policy, health administration and curriculum decisions related to reproductive health, and raise awareness about the crucial role of nurse practitioners in abortion care and contributions to reproductive health equity. Patient or Public Contribution: This study focused on provider experiences. In‐kind support was provided by Action Canada for Sexual Health & Rights, an organization that provides direct support and resources to the public and is committed to advocating on behalf of patients and the public seeking sexual and reproductive health services.